2012
DOI: 10.1111/j.1365-3180.2012.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter of the invasive Casuarina equisetifolia decomposes at the same rate as that of native woody species on oceanic islands but releases more nitrogen

Abstract: Hata K, Kato H & Kachi N (2012). Leaf litter of the invasive Casuarina equisetifolia decomposes at the same rate as that of native woody species on oceanic islands but releases more nitrogen. Weed Research52, 542–550. Summary We tested whether the decomposition rates and N loss of leaf litter of an alien invasive tree, Casuarina equisetifolia, are affected by litter traits and environmental conditions in the Ogasawara Islands in the north‐western Pacific Ocean. In a field experiment, we compared mass loss and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Microbial-aided decomposition of exotic litter of some invaders may lead to higher release of nutrients upon compared with native litter as a consequence of greater organic C in soil ( Ehrenfeld et al 2005 ; Hata et al . 2012 ; Kaur et al 2012 ; Meisner et al .…”
Section: Indirect Plant–soil Feedbacksmentioning
confidence: 99%
“…Microbial-aided decomposition of exotic litter of some invaders may lead to higher release of nutrients upon compared with native litter as a consequence of greater organic C in soil ( Ehrenfeld et al 2005 ; Hata et al . 2012 ; Kaur et al 2012 ; Meisner et al .…”
Section: Indirect Plant–soil Feedbacksmentioning
confidence: 99%
“…Casuarina equisetifolia has been shown to reduce insect species richness and alter species composition (Sugiura et al 2013). A recent study conducted by Hata et al (2012) on Chichijima Island in the subtropical Ogasawara (Bonin) Islands showed that litter decomposition of C. equisetifolia may alter nitrogen cycling in invaded forest ecosystems.…”
Section: Impacts Of Casuarinas In Their New Rangesmentioning
confidence: 99%
“…Invasion by A. adenophora did not affect gene expression levels associated with microbial nitrogen fixation, ammonia oxidation, and nitrite and nitrate reduction in the invaded soil. There was no evidence for the increased expression of N metabolic genes, which may also reflect high amounts of organic C (litter) present in the RSM of A. adenophora (Table 1), where its decomposition may release organic N in higher amounts than from either native plants, as reported for other invasive plant species (Ehrenfeld, Ravit & Elgersma, 2005;Hata, Kato & Kachi, 2012;Kaur et al, 2012;Meisner et al, 2012;Li et al, 2017). This is supported by evidence that more genes are associated with carbohydrate metabolism in the RSM of A. adenophora than in those of the native plant species.…”
Section: Discussionmentioning
confidence: 84%